Organizational culture aspects that facilitate lean implementation: a pilot study - Alkhoraif, Abdullah; McLaughlin, Patrick (Inderscience, 2018)
The paper aims to identify enablers and inhibitors of Lean Implementation (LI) in a small and medium-sized manufacturing (SME) organisation in Saudi Arabia. The paper opted for an exploratory study using the semi-structure interview approach of grounded theory, including seven in-depth interviews with employees representing from top management to the workers in the workshop having mainly an experience of Lean Implementation background. The data was complemented by context analysis, including simultaneous and concurrent data collection and constant comparison methods. It suggests successful communication and teamwork. However, there were two codes which had not been evidenced in prior research and were not identified in the literature review. These include; 'multiple decision makers' and the 'family effect'. This paper fulfils an identified need to study how organisational culture affects LI. It demonstrates the current state of LI in manufacturing companies by uncovering the enablers and inhibitors of organisational culture.
Keywords: organisational culture; OC; lean implementation; LI; enablers and inhibitors; small and medium-sized enterprises; SMEs; pilot study